Het spaar- en kredietprogramma van de Vredeseilanden / Rafia in Noord-Togo: Een kritische evaluatie. - Van Damme, Patrick; Hatsé, Ingrid (Afrika Focus, 1996)
Northern Togo has never been over-assisted as some of the other dry and poor areas of West Africa have been. It has never been a priority of national or international development organisations. As a consequence, the area has intermittent food security problems. Islands of Peace (Vredeseilanden), a Flemish NGO for development cooperation, however, has initiated a (successful) savings and credit scheme based on local surpluses which now allows local populations to invest and consolidate their (food security) situation. KEYWORDS : tontines, informal savings, rural credit, sustained development